CLAG3 Self-Associates in Malaria Parasites and Quantitatively Determines Nutrient Uptake Channels at the Host Membrane - Ankit Gupta (American Society for Microbiology, 2018)
ABSTRACT Malaria parasites increase host erythrocyte permeability to ions and nutrients via a broad-selectivity channel known as the plasmodial surface anion channel (PSAC), linked to parasite-encoded CLAG3 and two associated proteins. These proteins lack the multiple transmembrane domains typically present in channel-forming proteins, raising doubts about their precise roles. Using the virulent human Plasmodium falciparum parasite, we report that CLAG3 undergoes self-association and that this protein’s expression determines channel phenotype quantitatively. We overcame epigenetic silencing of clag3 paralogs and engineered parasites that express two CLAG3 isoforms simultaneously. Stoichiometric expression of these isoforms yielded intermediate channel phenotypes, in agreement with observed trafficking of both proteins to the host membrane. Coimmunoprecipitation and surface labeling revealed formation of CLAG3 oligomers. In vitro selections applied to these transfectant lines yielded distinct mutants with correlated changes in channel activity. These findings support involvement of the identified oligomers in PSAC formation and parasite nutrient acquisition. IMPORTANCE Malaria parasites are globally important pathogens that evade host immunity by replicating within circulating erythrocytes. To facilitate intracellular growth, these parasites increase erythrocyte nutrient uptake through an unusual ion channel. The parasite CLAG3 protein is a key determinant of this channel, but its lack of homology to known ion channels has raised questions about possible mechanisms. Using a new method that allows simultaneous expression of two different CLAG3 proteins, we identify self-association of CLAG3. The two expressed isoforms faithfully traffic to and insert in the host membrane, while remaining associated with two unrelated parasite proteins. Both the channel phenotypes and molecular changes produced upon selections with a highly specific channel inhibitor are consistent with a multiprotein complex that forms the nutrient pore. These studies support direct involvement of the CLAG3 protein in channel formation and are relevant to antimalarial drug discovery projects targeting parasite nutrient acquisition.